Quantifying tree height and canopy structure in a forest in Davao Oriental State College of Science and Technology, Mati City, Davao Oriental - Rancil Quin Salang (Davao Research Journal)
Forests are landscapes dominated by trees and cover approximately 30% of the earth’s land surface, housing most of its biodiversity. This study aimed to quantify the tree height and canopy structure of a man-made forest in the locality, particularly the density, relative density, frequency, relative frequency, coverage, relative coverage, diversity, and importance value of the trees in the study area. The establishment of the study area was conducted on September 8, 2017, a period of one day and a transect-quadrat method was employed to assess the trees in the forest. Two (2) species of tree were found in the study area. These were Gmelina (Gmelina arborea) and Mahogany (Swietenia macrophylia). The densest tree species was Mahogany with 0.53 followed by Gmelina with 0.47. Mahogany was also observed to have a higher frequency than Gmelina. Gmelina in the study area has larger canopy coverage and circumference at breast height than Mahogany attributed to its fast-growing nature. The diversity of tree species in the study area was found to be low, attaining only 0.47 on the Shannon-Wiener Diversity Index and 0.69 on Simpson’s Diversity Index due to the small number of tree species present. The results of the importance value were low, with 1.32 for Gmelina and 1.68 for Mahogany since they are relatively young and have similar numbers of individuals.